Characterization and quantification of iron species in the banded iron formations (BIFs) in China Craton to explore the potential for H2 production using XRD and Mössbauer spectroscopy - Hyo-Im Kim; Inkyeong Moon; Minkyeong Kim; Hyuk Jun Lee; Hyunkyung Choi; Young Rang Uhm; Lei Liu; Jonguk Kim; Wonnyon Kim (PLoS ONE, 2025)
Banded iron formations (BIFs), significant iron ore deposits formed approximately 2.3 billion years ago under low-oxygen conditions, have recently gained attention as potential geological sources for evaluating hydrogen (H₂) production. BIFs are characterized by high concentrations of iron oxide (20 to 40 wt.%) and low Fe3⁺/Fetot ratios, representing a major source of ferrous iron on Earth. This study investigates the mineralogical and geochemical characteristics of iron ore samples from the Wugang and Hengyang BIFs in China using X-ray diffraction (XRD) and Mössbauer spectroscopy to examine H2 generation potential. XRD analysis and microscopic observations showed that the magnetite and hematite are the primary ore minerals in BIFs in China Craton. Mössbauer spectroscopic results provided the quantified information on the fractions of each iron species in varying minerals. Particularly, the Fe3+ tetrahedral sites and octahedral sites occupied by both Fe2+ and Fe3+ in magnetite and Fe3+ octahedral sites in hematite were determined. We estimated H₂ production potential by calculating the relative fraction of Fe2+ in magnetite relative to total number of iron atoms in the bulk samples from the Mössbauer results. The pyroxene-bearing BIF in Wugang (P-BIF) contains magnetite predominantly (~30.4 wt%), and the fraction of Fe2+ in magnetite is ~26%. Based on the quantified values, the maximum potential for H2 generation from P-BIF in Wugang could be ~630 mmol H₂/kg rock. Due to the variation of mineralogical composition depending on the types and locations of occurrence of BIF, the H2 generation potential also varies. For example, contrast to P-BIF in Wugang, the hematite-rich BIF from Hengyang, containing ~6.0 wt% of magnetite, showed significantly lower Fe2+ fraction in magnetite (~5%), resulting in low H2 potential (~120 mmol H₂/kg rock). This study presents that a prevalence of magnetite in BIFs has considerable potential for H₂ production due to low Fe3+/Fetot, suggesting that the magnetite-rich iron ore can be effectively utilized as the source of stimulated hydrogen production. The current results also highlight that the Mössbauer spectroscopy is essential to provide the database of relative fractions for each iron species in BIFs, which allows us to estimate the quantity of H2 released from BIFs.